Pornography in Universalism Perspective: A Freedom Expression? - Eka N.A.M. Sihombing; Cynthia Hadita (Jurnal HAM, 2022)
The issue of the right to freedom of expression and pornography needs to be studied from a human rights perspective in terms of universalism and particularism. Pornography has the potential to have different standards depending on the time and place of a person's use of clothing and the extent to which the law restricts pornographic behavior. This study aims to unravel pornography and freedom of expression in the digital space from the Perspective of Human Rights Particularism. The research method used is normative legal research. The results reveal that freedom of expression in Indonesia is intertwined with the dimension of human rights particularism, especially Pancasila so all forms of protests that contain pornography disseminated through the digital space are contrast to the value of Indonesian human rights particularism.